(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Air pollution must take more attention because its effects on human health. One of the most important air pollutants is ground-level ozone O3, which plays an important role in air quality and climate change on the earth. Ozone affected by the other air pollutants, so this paper attempt to study the relationship between hourly, daily and monthly ground-level ozone concentration and hourly, daily and monthly air pollutant concentrations and its effect on ground-level ozone concentration. The other air pollutants are: sulfur dioxide SO2, nitrogen oxides NOx, nitrogen monoxide NO, nitrogen dioxide NO2 and carbon dioxide CO2. The monitoring station is in Babylon University in the south of Al-Hilla city, Iraq for the period 2015-2016. By using statistical analysis, correlation coefficient and some statistics for all air pollutants are computed. Results are: the maximum average ozone concentration is in the summer months June, July and August 39.30 ppb, 45.05 ppb and 36.63 ppb respectively and along the day the peak average ozone concentration is in the afternoon because of high temperature and high solar radiation intensity which is increasing the photochemical activity of ozone. There is no significant correlation between ozone and sulfur dioxide SO2, carbon dioxide CO2 (ρ > 0.05). High significant correlation is appeared between ozone and nitrogen oxides forms (ρ < 0.01). To express the complex relation between ozone and nitrogen oxide forms, proportions such as NO/NO2 and (NOx-NO)/NO is determined which explain the ozone photochemical activity. Ozone concentration decreases with increasing of NO/NO2 and increases with (NOx-NO)/NOx increasing.